Exploring a new preparation pathway for the synthesis of silica based xerogels as crack-free monoliths. Issue 2 (1st February 2019) - Çok, Selay Sert; Koç, Fatoş; Balkan, Firuz; Gizli, Nilay
Abstract: Comprehensive investigations to achieve monolithic silica xerogels in crack-free form under ambient conditions were carried out. Seven silica xerogels (SXs) were synthesized by following two different production pathways (one-step, two-step) by changing the type of the sol components. Morphological and chemical characteristics of the silica xerogels were revealed with the aid of the FTIR, EDX, Contact Angle, SEM, TGA and BET analyses. Imidazolium based ionic liquids (ILs) were incorporated into the xerogel structure to serve as drying control chemical, as well as to promote spring-back effect during the solvent evaporation. Amine based silica source 3-aminopropyltriethoxysilane (APTES) was also included as a silica co-precursor to improve the silica network. Surface modifications of final product were conducted by using 3-Methacryloxypropyltrimethoxysilane (MEMO) in order to transform the sample into hydrophobic characteristics. Visual observations were used as an instructive step to examine the monolithicity of the final product. As a result, volumetric ratio of the sol components (TEOS: APTES: IL: Ethanol: HCI) to achieve desired crack-free monolithic form with superior characteristics was determined as 1: 0.47: 0.1: 6.3: 7.4 × 10 −5, respectively.